EFFECT OF BENZALDEHYDE EXCESS IN THE SYNTHESIS OF LR-2 AND CYTOTOXIC ACTIVITY OF LR-2 AGAINTS HeLa CELL - Ritmaleni, Ritmaleni; Arifin, Muhammad Fajar; Laksmiani, Ni Putu Linda; ., Rumiyati; ., Sismindari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
LR-2(4-phenyl-3,4-dihydro-indeno[2â,1â]pyramidine-2(1H)- thione;Â LeniÂ RitmaleniÂ 2),Â whichÂ designedÂ andÂ assumedÂ toÂ have biologicallyÂ activityÂ asÂ anticancer,Â hasÂ beenÂ successfully synthesizedÂ byÂ usingÂ theÂ BiginelliÂ reaction.Â ThisÂ researchÂ was aimedÂ toÂ investigateÂ theÂ effectÂ ofÂ benzaldehydeÂ excessÂ inÂ the synthesisÂ ofÂ LR-2Â andÂ toÂ evaluateÂ theÂ cytotoxicÂ activityÂ ofÂ LR-2against HeLa cancer cell lines. The synthesis was done by reacting benzaldehyde, 2-indanone and togetherÂ with thiourea at one time asÂ saidÂ asÂ oneÂ potÂ reactionÂ syntheticÂ methodologyÂ andÂ the reaction was acid catalysed. The mole equivalent of benzaldehyde wasÂ inÂ excessÂ compareÂ toÂ others.Â TheÂ effectÂ ofÂ benzaldehydeÂ in excess is the higher the mole of benzaldehyde, the lower the yield ofÂ LR-2.Â TheÂ cytotoxicityÂ ofÂ LR-2Â wasÂ doneÂ byÂ usingÂ MTTÂ method and the LC50 was 268.15 Î¼M.Key words : LR-2, benzaldehyde, cytotoxic, HeLaÂ